PENGGUNAAN VIDEO ANIMASI SEBAGAI MEDIA PEMBELAJARAN PENGENALAN HURUF HIJAIYAH DI TADIKA SINAR AL-FIKH ORCHARD BANDAR PARKLANDS KLANG, MALAYSIA - Syatila Zahra; Hasrian Rudi Setiawan (Ilmuna: Jurnal Studi Pendidikan Agama Islam, 2025)
This study aims to determine the planning, implementation and evaluation in the use of animated video as a learning media for the introduction of Hijaiyah letters at Tadika Sinar Al-Fikh Orchard Bandar Parklands Klang, Malayasia. Where this research uses descriptive qualitative methods. Data collection techniques are carried out by interview and observation methods. In activities at Tadika Sinar Al-Fikh Orchard Bandar Parklands Klang, Malaysia, the use of animated video media is one of the media chosen in delivering learning materials. The use of animated videos can increase students' interest in learning and their understanding of the material presented in the video. Supporting factors such as facilities and Teacher's ability can support the use of animated video media optimally. In its implementation, the animated video is played for 15 minutes every Friday. While on other days, students get to know letters through printed media such as iqra' and posters. That is what makes learners not recognise hijaiyah letters optimally. Although learners are able to recognise the sound and shape of hijaiyah letters during video playback, they still have difficulty when asked